Post-Fire Compression Properties Of Sandwich Composite Material - Zainul, Abdul Rahman (Universiti Sains Malaysia, 2017)
The primary objective of this final year project is to investigate the post-fire, mechanical properties of sandwich composite which is a structure that is widely used in aircraft and spacecraft. In this project, E-glass reinforced epoxy laminate has been used as the composite skin and a plastic honeycomb for the core of the composite specimen. By applying fire, structural experiment method, this project investigates the behavior of sandwich composite after exposure to fire (post-fire). The experiment conduct of this project is to simulate the post-fire effect of on the sandwich composites. The effects of increasing exposure times on the residual compressive properties of the sandwich composite are experimentally determined. To investigate the mechanical properties, the compression test method was used to measure the stress, strain and young modulus of the sandwich composite. Compression test was performed for specimen at room condition first to select the suitable length. Next, specimen with suitable length was exposed to fire at different times and compression test was performed to find out the mechanical properties. Moreover, burn-off test also was conducted in this project to identify the fiber volume fraction of laminate layers of sandwich composite. It was found that the stress, strain and young modulus of sandwich composite decrease when exposed to fire at increasing the time. While for the burn-off test, the fiber volume fraction is obtaining around 40% to 46%.